Images and perceptions of fascism among the mainstream Kemalist elite in Turkey, 1931-1943 - Ünver, Cennet. (Thesis (M. A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2001., 2001)
The image and perception of Italian Fascism and German National Socialism, as it comes to an expression mainly in the official organs of the Republican People's Party, Hakimiyet-i Milliye (Ulus) and Ülkü, and partly in the influential journal Kadro constitutes the subject of this study. The thirteen year period beyween 1931 and 1943, in which the authoritarian character of the single-party regime in Turkey was most evident, is the time frame. The approach to fascist ideology, the topics attracting most attention, and the way some of the core elements in Fascism and National Socialism are described in these sources, is identified in the work, which with a disclaim of undertaking a comparative analysis, still claims to include a comparative aspect. The particular interest in Italian Fascism in the first half of the 1930s, the positive perception of notions such as discipline, organization of the youth, ideological and physical education, the role of leaders, and finally, seen in general, the absence of any critical stance toward the two fascist regimes, are some of the findings which stand out in the examination of the sources. With this different approach to the experience of single-party rule in Turkey, this study brings to attention a new aspect and contributes to the wider debate over the authoritarian nature of the Kemalist regime in the inter-war period.
Keywords: Fascism -- Italy.; Fascism -- Turkey -- History -- 20th century.; National socialism -- History.